INTEGRATION OF ARTIFICIAL INTELLIGENCE IN SUPPLY CHAIN MANAGEMENT: CHALLENGES AND OPPORTUNITIES - G Anuradha Reddy; M Shankar Lingam, (International Journal of Advances in Business and Management Research (IJABMR), 2025)
This article looks at how Artificial Intelligence (AI) is transforming Supply Chain Management (SCM). It provides a deep perspective into the current trends, challenges, and opportunities that AI is bringing to the supply chain world. By reviewing academic studies and industry reports, the article sheds light on what the future of SCM could look like as AI continues to evolve. The integration of AI in SCM marks a major shift in how businesses run their operations, manage resources, and meet customer needs. This article examines both the opportunities and challenges that come with adopting AI in supply chains. While AI holds promises for improving efficiency, refining demand forecasting, optimising inventory, and streamlining logistics, there are hurdles to overcome. These include the hefty upfront investment required, issues with data quality, the need for AI literacy, and concerns over data privacy and automation. Through a detailed review of academic research, industry reports, and case studies, the article provides a well-rounded view of AI's current role in SCM. It highlights how AI technologies—like machine learning, natural language processing, and robotics—are already being used to improve decision-making, transparency, and customer satisfaction. Additionally, the article discusses strategies businesses can use to overcome the challenges of AI adoption. These include investing in human capital, ensuring ethical AI use, and promoting technological interoperability.